Effect of nano thermal barrier coatings on the thermal-structural performance of ω-shaped internal combustion engine piston - Zhimin Yao; Peng Zhang; Jialong Liu; Yining Li; Mengjia Shao; Liqun Gao (Case Studies in Thermal Engineering)
Nano-coatings are used for thermal protection of internal combustion engines. This study investigates the thermal-structural performance of ω-shaped diesel engine pistons coated with 8 wt% YSZ nano-thermal barrier coatings (TBCs) using experimental and numerical methods. The results show that the TBCs increased the piston top temperature by 90 °C, while decreasing the substrate temperature by 28–48 °C, thus reducing the heat flux. Thermal stress analyses show that TBCs significantly reduce the stresses in the piston substrate. Peak equivalent and shear stresses occur at the ceramic-bonded coating interface, increasing the risk of cracking. In addition, TBCs effectively reduce the thermal deformation of the piston and improve its fitment to the cylinder liner. These findings offer valuable insights into the thermal-structural behavior of nanostructured TBCs in diesel engine pistons, underscoring their potential to improve engine performance and durability.